Counter Intelligence Corps history and mission in World War II. - Counter Intelligence Corps School (1940)
Contains information on the historical development, function, and organization of the Counter Intelligence Corps and its missions in various theaters of operations. Including Zone of the Interior, North Africa, Europe, North Atlantic, Caribbean, South Atlantic, Middle East, China-Burma-India, Alaska, Hawaii, Southwest Pacific, and the Philippines.